2013
DOI: 10.1016/j.jhealeco.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Does hospital ownership affect patient experience? An investigation into public–private sector differences in England

Abstract: Using patient experience survey data, the paper investigates whether hospital ownership affects the level of quality reported by patients whose care is funded by the National Health Service in areas other than clinical quality. We estimate a switching regression model that accounts for (i) some observable characteristics of the patient and the hospital episode; (ii) selection into private hospitals; and (iii) unmeasured hospital characteristics captured by hospital fixed effects.We find that the experience rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 35 publications
2
48
2
Order By: Relevance
“…An empirical study in the USA revealed that private hospitals provide a better hospital environment with quieter and cleaner rooms, while nonprofit hospitals have lower mortality and readmission rates (Ding, ). Similar results were found by empirical studies in the UK (Pérotin, Zamora, Reeves, Bartlett, & Allen, ) and Taiwan (Lien, Chou, & Liu, ).…”
Section: Literature Reviewsupporting
confidence: 88%
“…An empirical study in the USA revealed that private hospitals provide a better hospital environment with quieter and cleaner rooms, while nonprofit hospitals have lower mortality and readmission rates (Ding, ). Similar results were found by empirical studies in the UK (Pérotin, Zamora, Reeves, Bartlett, & Allen, ) and Taiwan (Lien, Chou, & Liu, ).…”
Section: Literature Reviewsupporting
confidence: 88%
“…However, Pérotin did not find a significant difference on the reported overall patient experiences between public and private clinics. Differences that were found seemed to relate to other variables such as patient characteristics …”
Section: Resultsmentioning
confidence: 99%
“…Both Pérotin et al and Owusu‐Frimpong et al examine UK patient experiences. The latter study finds that users of ISTCs have higher satisfaction rates than the users of public facilities for amenities, for instance, obtaining attention from doctors .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…taking account of the differences between the patient groups treated in ISTCs, as compared to NHS facilities) might have been insufficient. Recently, Perotin et al (2010) have used another data set to investigate the quality of care provided by ISTCS compared to NHS services. This data comes from the Patient Experience Survey, which is carried out annually among NHS and ISTC patients.…”
Section: Introduction: Policy Of Increasing Diversity Of Providers Inmentioning
confidence: 99%